Speaking Skills Improvement Through the Role-Play Method in MTs Negeri 3 Probolinggo - Imro Atus Soliha; Nur Khosiah; Pratiwi Dwi Warih Sitaresmi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Speaking is one of the skills in learning English languages ​​besides the other 3 skills in language: listening, reading, and writing. The four skills are connected, and the connection influences each other. Speaking skill talk about the art of speaking in conveying messages, ideas, and thoughts, for various purposes such as reporting, entertaining, persuading, or inviting others people. By speaking, people interact and create social relations between two or more people. This type of research is classroom action research to find out the improvement of students' English proficiency by using the role-play method. The sample of this research is students at eight grade from MTSN 2 Probolinggo in the academic year 2021/2022. To analyze the data, it used the Mean formula in calculating the average score of students with Criteria, if the average minimum score of 75% and improved in each cycle, then that role-playing method works. The results show that students' average score on speaking tests in the first cycle is 77.0, an increase of about 11.32 points from a pre-action class, and improved by 4.9 points to 81.9 in the second cycle. The minimum number of students who pass the criteria in the first cycle is 12 students and 16 students in the second cycle. It means the role-playing method can improve students' English-speaking skills, and the percentage of improvements has reached 88,9% of all students, then the action class research was stopped in the second cycle.